2019
DOI: 10.1002/hep.30342
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diverse Hepatitis C Strains Detected in Sub‐Saharan Africa Have Unknown Susceptibility to Direct‐Acting Antiviral Treatments

Abstract: The global plan to eradicate hepatitis C virus (HCV) led by the World Health Organization outlines the use of highly effective direct‐acting antiviral drugs (DAAs) to achieve elimination by 2030. Identifying individuals with active disease and investigation of the breadth of diversity of the virus in sub‐Saharan Africa (SSA) is essential as genotypes in this region (where very few clinical trials have been carried out) are distinct from those found in other parts of the world. We undertook a population‐based, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…This is concordant with recent data from a cohort from Uganda and the Democratic Republic of Congo, where highly diverse genotype 4 and 7 strains, including unconfirmed novel strains were recently identified. 2 We can speculate that the diversity of HCV observed in this cohort and other studies, if confirmed by larger phylogenetic analyses, perhaps points to an early evolutionary origin of human hepatitis C genotype 1 and 4 in Africa. 13 We observed a high number of resistance-associated polymorphisms in pre-treatment samples from our cohort.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is concordant with recent data from a cohort from Uganda and the Democratic Republic of Congo, where highly diverse genotype 4 and 7 strains, including unconfirmed novel strains were recently identified. 2 We can speculate that the diversity of HCV observed in this cohort and other studies, if confirmed by larger phylogenetic analyses, perhaps points to an early evolutionary origin of human hepatitis C genotype 1 and 4 in Africa. 13 We observed a high number of resistance-associated polymorphisms in pre-treatment samples from our cohort.…”
Section: Discussionsupporting
confidence: 74%
“…1 Despite this, there have been few clinical trials conducted in African cohorts and data is lacking on the prevalence, geographical distribution and treatment response of African sub-genotypes. 2,3 There are 8 known HCV genotypes which have been classified based on the analysis of HCV genetic sequences. 4 Except for genotypes 5 and 8, each genotype is further divided into a number of subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Most GT-4 subtype diversity is observed in sub-Saharan Africa, with GT-4r, for example, frequently found in the DRC and Rwanda. [23] Most of our black GT-4 patients originated from these and other African countries, explaining our observed diversity. Other unusual subtypes, e.g.…”
Section: Researchmentioning
confidence: 72%
“…A consistent, unified approach to classification will advance this field, improving consistency of curating, archiving and reporting sequence data. Recent work sampling poorly accessed populations has uncovered numerous new HCV isolates (41,42), and the diversity of sequences generated for HBV may expand in a similar way. The use of a robust and consistent classification system will also be important in screening new populations for potentially novel HBV isolates.…”
Section: Resultsmentioning
confidence: 99%